Experts Discuss the Promises and Challenges with Targeted Therapies - Powers, Jenny (MD Conference Express, 2014)
This article discusses targeted therapies in non—small cell lung cancer (NSCLC), including the rise and partial fall in efficacy seen with tyrosine kinase inhibitors (TKIs) of the anaplastic lymphoma kinase (ALK) pathway. Other topics include a review of strategies to target the epidermal growth factor receptor (EGFR), as well as the challenge of targeting new pathways.